Construction of stable HeLa cell lines for the identification of enzyme-induced bias in proximity-dependent labeling techniques - Enno Große Wichtrup (2023)
While different optimized biotin protein ligases (BPL) for proximity dependent labeling techniques are increasingly used in fundamental research, whether or not these enzymes induce bias through their interaction with host cell components has not yet been adequately explored. This thesis aims to construct the tools which will allow to investigate whether four different BPL´s, used in proximity dependent labeling techniques, could influence the correct targeting of a protein of interest (POI), because of their interaction with cell components. For this purpose, four stable HeLa cell lines were constructed containing the genetic information for the BPL´s BioID2, TurboID, UltraID or BASU, fused only to a myc-tag, in their genomes. By using the recombinase mediated cassette exchange (RMCE) as the transfection method the isogenicity and with that the comparability of the results was preserved. By varying the dose of the transcriptional activator doxycycline, the dose-response on the expression of enzymes was investigated. Biotinylated proteins were analyzed by western blot, using horseradish peroxidase (HRP) conjugated streptavidin. This allowed a direct comparison of the biotinylation activities of the different enzymes. All four stable cell lines were constructed successfully and induction was achieved as assumed. For UltraID and TurboID enhanced biotinylation of certain proteins were detected, thus suggesting that enzyme-induced bias may occur.